Comparison of Incidence of Laryngospasm between Laryngeal Mask Airway and Endotracheal Tube during the Recovery Phase following Urological Procedure in Paediatric Patients - Bhowmick, Lipon Kanti; Mahabubuzzaman, Mohammad; Islam, Md Saiful; Begum, Sharmin Ara; Babu, Md Ishaq; Tuhin, Shafiqul Bari; Hasan, Mahmud Javed (Community Based Medical Journal, 2024)
Airway-related issues pose significant perioperative complications in paediatric anaesthesia, with laryngospasm being particularly noteworthy. The choice of airway device has been identified as a contributing factor to this concern. This research was conducted from January to December of 2023; it specifically investigated and compared the incidence of laryngospasm following removal of a laryngeal mask airway (LMA) versus an endotracheal tube (ET) in paediatric patients undergoing elective urological procedure. Sixty ASA – I/II patients, aged 2 to 5 years and of both genders, were randomly allocated into two groups: Group I received ETT, while Group II received LMA. Various parameters including hemodynamic measures and the occurrence of laryngospasm, cough, and other complications were assessed. Results demonstrated a higher incidence of laryngospasm and cough in the ET group compared to the LMA group (p<0.05). However, no significant differences were observed between the groups regarding other complications such as bradycardia, apnoea, desaturation, shivering, and abdominal distension. Adoption of a laryngeal mask airway (LMA) instead of an endotracheal tube (ET) during elective urological procedures in paediatric patients may lead to a lower occurrence of laryngospasm. CBMJ 2024 July: vol. 13 no. 02 P: 183-191